2022
DOI: 10.1155/2022/3969165
|View full text |Cite
|
Sign up to set email alerts
|

Do Pollination and Pollen Sources Affect Fig Seed Set and Quality? First Attempt Using Chemical and Vibrational Fingerprints Coupled with Chemometrics

Abstract: This research investigates whether pollination and pollen sources separately and simultaneously influence fig seed set and quality, as being thus far the less studied part of the fig trees. This is the first research that tries to answer and verify the above hypothesis through a combined approach of vibrational spectroscopy along with lipo-biochemical and ionomic fingerprinting. Results showed that pollination and pollen source significantly impacted seed set as it was higher in fertilized seeds than that in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 75 publications
1
7
0
Order By: Relevance
“…Richness of fig seeds in proteins and mineral elements has already been reported (Duman et al, 2018;Nakilcioglu-Tas, 2019;Bölek, 2020); also, the effect of pollination on their content (Hssaini et al, 2022). Ustun-Argon et al (2021) report that Potassium, Magnesium and Calcium were the main mineral compounds in the dried fig seeds.…”
Section: Proteins and Mineral Contentmentioning
confidence: 84%
See 2 more Smart Citations
“…Richness of fig seeds in proteins and mineral elements has already been reported (Duman et al, 2018;Nakilcioglu-Tas, 2019;Bölek, 2020); also, the effect of pollination on their content (Hssaini et al, 2022). Ustun-Argon et al (2021) report that Potassium, Magnesium and Calcium were the main mineral compounds in the dried fig seeds.…”
Section: Proteins and Mineral Contentmentioning
confidence: 84%
“…These seeds, which vary in number and size, play a crucial role in determining the flavor and taste of figs, as well as their nutritional composition. These aspects are influenced by several factors, including the genotype of the fig, its ripening stage, and the mutualistic relationship between the fig and its pollinator wasp, which is known as caprification (Solomon et al, 2006;Gaaliche et al, 2011;Rosianski et al, 2016;Hssaini et al, 2022). Despite their contribution to the nutritional composition of figs, there have been very few studies on fig seeds (Hssaini et al, 2020;Hssaini et al, 2021a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These seeds, which vary in number and size, play a crucial role in determining the flavor and taste of figs, as well as their nutritional composition. These aspects are influenced by several factors, including the genotype of the fig, its ripening stage, and the mutualistic relationship between the fig and its pollinator wasp, which is known as caprification (Solomon et al, 2006;Gaaliche et al, 2011;Rosianski et al, 2016;Hssaini et al, 2022). Despite their contribution to the nutritional composition of figs, there have been very few studies on fig seeds (Hssaini et al, 2020;Hssaini et al, 2021a).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has shown that fig seed oil is generally pale yellow in color and yields can vary significantly based on the genotype, with some genotypes yielding up to 30% oil content (Hssaini et al, 2020). The macro-qualitative components of fig seeds, including oil yield and lipochemical composition, are influenced by both genetic differences between seeds and geographical variations (Raihana et al, 2015;Górnaśand Rudzińska, 2016) as well as the pollination system (Hssaini et al, 2022). Compared to other fruit seeds, fig seeds have an oil yield that is similar to pumpkin (27.83%) (Alfawaz, 2004), honeydew (25%) (Yanty et al, 2008), and mangosteen (21.18%) (Ajayi et al, 2007), and higher than those of durian seeds (1.8%) (Berry, 1980), Opuntia ficus indica seeds (5.4 to 9.9%) (Taoufik et al, 2015), and guava (16%) (Prasad and Azeemoddin, 1994).…”
Section: Introductionmentioning
confidence: 99%